Disinverting moralized authoritarian governance: Truth, verification, and non-Teleological pathways of destabilization - Sissoko, Étienne Fakaba; Bayo, Pierre (Revue Internationale des Sciences de Gestion, 2026)
This article conceptualizes a form of authoritarian fragility that remains obscured when institutional persistence is equated with political stability. It introduces the concept of moral disinversion to designate an endogenous, reversible, and non-teleological process through which moralized authoritarian governance loses its capacity to convert narrative loyalty into moral adhesion, without necessarily producing democratic transition, institutional collapse, or organized resistance. The central claim is that obedience may persist while belief withdraws. The article positions this concept in relation to scholarship on authoritarian stability, informational autocracy, symbolic domination, and infra-political practices. It then identifies five observable mechanisms: narrative–experience dissonance, moral fatigue, symbolic desacralization, fragmentary reactivation of verification practices, and obedience–belief dissociation. Finally, it distinguishes between two logics for managing this fragility, patriotic resilience and informational resilience, before proposing a non-teleological typology of possible configurations. The article’s main contribution is to make observable a moral form of fragility under authoritarian continuity.